Description of Two Novel Henneguya (Cnidaria: Myxosporea) Infecting Curimatid Fish, Using Morphological, Histological, and Molecular Analyses - Vieira, Diego Henrique Mirandola Dias [UNESP]; Narciso, Rodrigo Bravin [UNESP]; de Azevedo, Rodney Kozlowiski; da Silva, Reinaldo José [UNESP] (Springer Nature, 2022)
Purpose: We describe two new Henneguya spp. (Myxobolidae) found parasitizing Cyphocharax modestus from Pardo river, Paraná river basin, municipality of Botucatu, São Paulo State, Brazil: Henneguya fastigata n. sp. from gill lamellae and Henneguya pardensis n. sp. from gill arches. We based the descriptions on myxospore morphology, histology, and small subunit ribosomal DNA sequences. Methods: In this investigation, 50 specimens of Cyphocharax modestus were examined between July and December 2020 for myxozoan infections. Morphological characterization was based on the mature myxospores. The small subunit ribosomal DNA sequences were used for molecular and phylogenetic study. Results: Phylogenetic analysis provided the evolutionary position of these new species with other myxobolids species. Myxospores of the two species had similar morphology and morphometrics, but differed in spore body width and length, and ssrDNA sequences differed by 7.2%. These data supported the diagnosis of the parasites as distinct and novel species. The phylogenetic analysis showed a well-supported subclade formed by species that parasitize curimatid fishes, with Henneguya gilbert as a sister species of Henneguya fastigata n. sp., and Henneguya pardensis n. sp. as a sister species of both species. Conclusion: Our analysis was consistent with previous studies suggesting that orders and families of the hosts are strongly correlated with phylogenetic signals in the Myxobolidae. These are the first species of myxozoans described in the Pardo river.
Keywords: Curimatidae; Gills; Myxobolidae; Pardo river; Phylogeny